Religious Minorities in the Middle East Domination, Self-Empowerment, Accommodation - Roald, Anne Sofie; Nga Longva, Anh (Brill, 2020)
The relationship between religious majorities and minorities in the Middle East is often construed as one of domination versus powerlessness. While this may indeed be the case, to claim that this is only or always so is to give a simplified picture of a complex reality. Such a description lays emphasis on the challenges faced by the minorities, while overlooking their astonishing ability to mobilize internal and external resources to meet these challenges. Through the study of strategies of domination, resilience, and accommodation among both Muslim and non-Muslim minorities, this volume throws into relief the inherently dynamic character of a relationship which is increasingly influenced by global events and global connections.